Comparative analysis of existing food safety culture evaluation systems. (September 2017) - Jespersen, Lone; Griffiths, Mansel; Wallace, Carol A.
Abstract: The purpose of the research was firstly, to analyze existing culture evaluation systems for commonalities and differences in research quality, applied validation strategies, and content. Secondly, to suggest a simple structure of food safety cultural dimensions to help unify the culture evaluation field. To achieve these goals, a comparison of eight culture evaluation models applied to varing degrees in the food industry was conducted. The systems were found to vary significantly in applied validation strategies but through deductive, textual data analysis, five dimensions were identified that cover elements present in all the models. Transparency is needed when using applied research methodologies to continually increase quality and trustworthiness of culture research in the food safety domain and this field would benefit from both further commonality of approach to validation strategy and structure and adoption of an overarching structural framework. Highlights: A discusion and application of standards for research quality and trustworthiness. Comparative analysis of eight organizational and food safety culture models. Common validation techniques and only two methods demonstrate predictive validity. Qualitative content analysis of each model to the published research guidelines. Framework of five cultural dimensions is proposed to unify the research field.